Lower‐limb muscle responses evoked with noisy vibrotactile foot sole stimulation - Peters, Ryan M. (Physiol Rep, 2020)
AIM: Cutaneous feedback from the foot sole contributes to the control of standing balance in two ways: it provides perceptual awareness of tactile perturbations at the interface with the ground (e.g., shifts in the pressure distribution, slips, etc.) and it reflexively activates lower‐motor neurons to trigger stabilizing postural responses. Here we focus on the latter, cutaneous (or cutaneomotor) reflex coupling in the lower limb. These reflexes have been studied most‐frequently with electrical pulse trains that bypass natural cutaneous mechanotransduction, stimulating cutaneous afferents in a largely non‐physiological manner. Harnessing the mechanical filtering properties of cutaneous afferents, we take a novel mechanical approach by applying supra‐threshold continuous noisy vibrotactile stimulation (NVS) to the medial forefoot. METHODS: Using NVS, we characterized the time and frequency domain properties of cutaneomotor reflexes in the Tibialis Anterior. We additionally measured stimulus‐triggered average muscle responses to repeated discrete sinusoidal pulses for comparison. To investigate cutaneomotor reflex gain scaling, stimuli were delivered at 3‐ or 10‐times perceptual threshold (PT), while participants held 12.5% or 25% of maximum voluntary contraction (MVC). RESULTS: Peak responses in the time domain were observed at lags reflecting transmission delay through a polysynaptic reflex pathway (~90–100 ms). Increasing the stimulus amplitude enhanced cutaneomotor coupling, likely by increasing afferent firing rates. Although greater background muscle contraction increased the overall amplitude of the evoked responses, it did not increase the proportion of the muscle response attributable to cutaneous input. CONCLUSION: Taken together, our findings support the use of NVS as a novel tool for probing the physiological properties of cutaneomotor reflex pathways.